Application of Immunotherapy in the Treatment of Solid Tumors - Zhang, Wenhan (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Cancer is one of the major diseases that seriously threaten human life and health at present, and the number of deaths due to cancer every year ranks in the top 2 of all diseases. In recent years, the malignant tumor is increasing year by year, so it is necessary to explore new therapeutic methods. Immunotherapy of tumor cells is one of the hot topics in tumor therapy, which aims to destroy tumor cells by activating or regulating the immune system of patients. More and more tumor immunotherapy drugs have been successfully developed and marketed, bringing the hope of long-term survival to patients. However, like other tumor drug therapy, tumor immunotherapy has brought huge benefits to some tumor patients and made people full of expectations, but it also faces many difficulties and challenges in pre-clinical research and clinical application. This article summarizes the application and challenge of immunotherapy in solid tumors.